Twenty four hour intragastric acidity and plasma gastrin concentration in healthy volunteers taking nizatidine 150 mg, nizatidine 300 mg, ranitidine 300 mg, or placebo at 21:00 h. Issue 10 (October 1988) - Lanzon-Miller, S; Pounder, R E; Chronos, N A; Raymond, F; Hamilton, M R; Dalgleish, D
Abstract : Nine healthy volunteers were studied on the seventh day of dosing at 21:00 h with nizatidine 150 mg (N 150), nizatidine 300 mg (N 300), ranitidine 300 mg (R 300), or placebo, given in a predetermined random order. The double-blind 24 hour studies, using the Royal Free Hospital standard protocol, simultaneously measured intragastric acidity and plasma gastrin concentration. Compared with placebo, subjects responded to dosing with each H2-antagonist by a significant decrease of 24 hour intragastric acidity (N 150-45%; N 300-49% R 300-56%; p less than 0.01) and a significant rise of plasma gastrin concentration (N 150 + 20%; N 300 + 27%; R 300 + 58%; p less than 0.01). All three drug regimens caused similar significant decreases of nocturnal acidity (N 150-72%; N 300-79%; R 300-85%; p less than 0.01) and increases of nocturnal plasma gastrin concentration (N 150 + 41%; N300 + 52%; R 300 + 80%; p less than 0.01). Dosing with ranitidine 300 mg at 21:00 h also caused a simultaneous significant decrease of morning acidity (-32%; p less than 0.05) with a significant increase of plasma gastrin concentration (+36%; p less than 0.05), but the antisecretory effects of nizatidine 150 or 300 mg at 21:00 h were only observed during the night, with no effect during the morning. No drug regimen had any effect on acidity or plasma gastrin in the afternoon or early evening.